Effect of rumen-escape protein level on feedlot performance and carcass traits of implanted vs nonimplanted yearling steers - Brandt, Robert T., Jr.; Reinhardt, Christopher D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred eighty yearling steers (743 lb) were blocked by weight; implanted with Synovex® (S), Synovex plus Finaplix® (SF), or not implanted (C); and fed diets containing 11.75% (L), 13.0% (M), or 14.25% (H) crude protein with all supplemental protein above 11.75% being supplied by corn gluten meal and blood meal in a 50:50 ratio (crude protein basis). An addition al protein level fed to S and SF implanted cattle was H for the first 70 days on feed and L thereafter (H-L). Animals were reimplanted on day 70. Steers treated with SF gained faster and more efficiently than non-implanted cattle. Differences in protein level had no effect on fat deposition in control steers, but cattle receiving SF and consuming M had more back fat and kidney, pelvic, heart (KPH) fat than those fed either H or L and also had more marbling than those fed H. Also, no apparent differences occurred between cattle fed M throughout the trial and those switched from H to L at 70 days.
Keywords: Beef; Estradiol; Trenbolone acetate; Implants; Escape protein; Protein level